Categorization of directional motion verbs - Waliński, Jacek (Categories and Units in Language and Linguistics, 2020)
This study presents a proposal of categorization of directional motion verbs, i.e. ones whose lexical semantics specifies a direction of motion, even without an overt directional complementation. The categorization proposed here includes (1) source/goal verbs, which are used to refer to bounded paths; (2) unbounded path verbs, which can be divided into two subgroups of upward/downward verbs and forward/backward verbs; (3) route verbs, which include cross and pass; (4) constant verbs, which again can be divided into two subgroups of chase verbs and accompany verbs; (5) deictic verbs, namely come and go, which are approached as a separate class. The proposal originates from previous studies conducted to this end in semantics, and is meant to encourage discussion on further advancement in this area of linguistic studies.